Chasing cardiac physiology and pathology down the CaMKII cascade - Mattiazzi, Alicia Ramona (2015)
Calcium dynamics is central in cardiac physiology, as the key event leading to the excitation-contraction coupling (ECC) and relaxation processes. The primary function of Ca2+ in the heart is the control of mechanical activity developed by the myofibril contractile apparatus. This key role of Ca2+ signaling explains the subtle and critical control of important events of ECC and relaxation, such as Ca2+ influx and SR Ca2+ release and uptake. The multifunctional Ca21-calmodulin-dependent protein kinase II (CaMKII) is a signaling molecule that regulates a diverse array of proteins involved not only in ECC and relaxation but also in cell death, transcriptional activation of hypertrophy, inflammation, and arrhythmias. CaMKII activity is triggered by an increase in intracellular Ca2+ levels. This activity can be sustained, creating molecular memory after the decline in Ca2+ concentration, by autophosphorylation of the enzyme, as well as by oxidation, glycosylation, and nitrosylation at different sites of the regulatory domain of the kinase. CaMKII activity is enhanced in several cardiac diseases, altering the signaling pathways by which CaMKII regulates the different fundamental proteins involved in functional and transcriptional cardiac processes. Dysregulation of these pathways constitutes a central mechanism of various cardiac disease phenomena, like apoptosis and necrosis during ischemia/reperfusion injury, digitalis exposure, post-acidosis and heart failure arrhythmias, or cardiac hypertrophy. Here we summarize significant aspects of the molecular physiology of CaMKII and provide a conceptual framework for understanding the role of the CaMKII cascade on Ca2+ regulation and dysregulation in cardiac health and disease.